Auxin (IAA) and soluble carbohydrate seasonal dynamics monitored during xylogenesis and phloemogenesis in Scots pine - Fajstavr M (iForest - Biogeosciences and Forestry, 2018)
The metabolic activity of phytohormones and the accumulation of carbohydrates affect the reactivation of the cambial zone and the radial increment of woody plants. We aimed to monitor the dynamics of indole-3-acetic acid (IAA) concentration and amounts of soluble carbohydrates during xylem and phloem formation of one growing season (2015). Six sample trees of Scots pine (Pinus sylvestris L.), aged 80 years on average, growing in the Sobešice research site (404 m a.s.l.) in the Czech Republic were selected. We obtained microcore samples at weekly intervals by the Trephor tool method for cell formation analysis and spectrophotometric determination of IAA and soluble carbohydrate contents. We found that time of the highest concentration of IAA (last week of April) coincided with time of the maximum number of cells in the cambial zone and highest expansion of the cell enlargement stage. When the IAA concentration was too low to be measured, latewood tracheids started to form, and late phloem sieve cell formation ceased. The highest concentration of soluble carbohydrates was 200.40 ± 21.6 µg GLU per sample (May 14). This coincided with the fastest weekly xylem cell increment. This research shows that IAA and soluble carbohydrate dynamics directly affects xylem and phloem formation.